Bioactive components of ethnomedicine Eerdun Wurile regulate the transcription of pro-inflammatory cytokines in microglia. (10th January 2020) - Qiburi, Qiburi; Ganbold, Tsogzolmaa; Bao, Qingming; Da, Man; Aoqier, Aoqier; Temuqile, Temuqile; Baigude, Huricha
Abstract: Ethnopharmacological relevance: The traditional Mongolian medicine Eerdun Wurile (EW) has remarkable neural recovery effect, and has been playing a key role in the clinical treatment of neurological disorders including ischemic stroke in Inner Mongolia Autonomous Region of China. The preliminary pharmacological studies in animal suggested that EW regulates the expression of trophic factors in brain lesion and may also balance the polarization of activated microglia (Gaowa et al., 2018). Aim of the study : The pool of leading bioactive chemicals underlying the therapeutic effects of EW has not been identified. Therefore, the mechanism of action of EW is poorly understood. This study was aimed to identify the major group of compounds that contribute to the inhibition of neuroinflammation during stroke recovery through regulation of microglia polarization. Materials and methods: The extracts of EW in different solvents were evaluated for their inhibitory ability of cytokine (IP-10) expression in LPS stimulated BV2 cells. The most effective extract (of petroleum ether extract) was further separated to 18 fractionations on a semi-preparative HPLC column, which were assess for the IP-10 down-regulation efficiency by RT-qPCR. The potent isolate was further fractionated in 12 fractions, which showed fewer peaks. The fraction 6 from this isolates, which remarkably down-regulates cytokines expression including IP-10, TNFα and IL-1β, was analyzed on UPLC-qTOF MS. The key chemicals were measured for their cytokine inhibition in BV2 cells and mouse primary microglia. Results: After two consecutive fractionating by preparative HPLC, petroleum ether extraction of EW gave 12 fractions with relatively distinctive chromatograms. A particular fraction (fraction 6) preserved the inhibitory effects on expression of pro-inflammatory cytokines including IP-10, TNFα, IL-1β and iNOS. The result of UPLC-qTOF MS analysis showed that the fraction contains 21 chemicals including costunolide, alantolactone, myristicin and linolenic acid, which significantly down-regulate the expression of key pro-inflammatory cytokines in LPS stimulated BV2 cells as well as mouse primary microglia. Conclusion: Collectively our data suggest that the bioactive chemical pool which is responsible for the therapeutic effects of EW can be extracted in petroleum ether, and fractionated to a relatively small multiple components. Such components include known anti-inflammatory chemicals, which may contribute to the possible microglia polarization in brain lesion during the recovery of ischemic stroke. Graphical abstract: Image 1